Compartmentalization of interphase chromosomes observed in simulation and experiment - Münkel, Christian; Eils, Roland; Langowski, Jörg (Journal of molecular biology, 2002)
Human interphase chromosomes were simulated as a flexible fiber with excluded volume interaction, which represents the chromatin fiber of each chromosome. For the higher-order structures, we assumed a folding into 120kb loops and an arrangement of these loops into rosette-like subcompartments. Chromosomes consist of subcompartments connected by small fragments of chromatin. Number and size of subcompartments correspond with chromosome bands in early prophase. We observed essentially separated chromosome arms in both our model calculations and confocal laser scanning microscopy, and measured the same overlap in simulation and experiment. Overlap, number and size of chromosome 15 subcompartments of our model chromosomes agree with subchromosomal foci composed of either early or late replicating chromatin, which were observed at all stages of the cell cycle and possibly provide a functionally relevant unit of chromosome territory compartmentalization. Computed distances of chromosome specific markers both onMb and 10-100Mb scale agree with fluorescent in situ hybridization measurements under different preparation conditions.
Elektronische Reproduktion der Druckausgabe
Gesehen am 23.04.2021